ANALISIS MODEL PEMBELAJARAN PEER LED GUIDED INQUIRY (PLGI) TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - Anita Wanevi; Nur Saimah Embu; Rita Farida (UNIVERSITAS SERAMBI MEKKAH, 2024)
In essence, students always have to understand concepts with problems that are the center of attention, but also gain learning experiences related to skills in applying scientific methods in solving problems in real life. Peer Led Guided Inquiry is a learning approach that involves students as tutors who guide their friends through an inquiry process to understand mathematical concepts in solving problems. The method used by the author in writing scientific articles is the literature study method. Research using the literature study method does not require researchers to go into the field to obtain respondent data. Researchers simply search for data through literature reviews, articles and documents. The results of the research are that there is an influence of the peer led guided inquiry learning model.